(untitled) (Journal of Parents and Teachers, 2025)
The article describes how reading is carried out, taking into account that through reading, one can access other lives and develop imagination. When discussing a classic, it is understood that it may present difficulties regarding linguistic, stylistic, or even content levels. Additionally, a selection of reading books is included, along with their respective summaries to provide examples.